Determination of Mixtures in Essential Oils in Laboratory Conditions (As Required By Df) - M., Mamadjanova; I. I, Zahiriddinov; O. N, Abdulatifova (American Journal of Biology and Natural Sciences, 2025)
This study investigates the quality assessment of lemon essential oil through laboratory-based solubility and impurity tests, addressing the need for reliable methods in essential oil purity analysis. While essential oils are widely used in medicine and industry, limited research explores systematic approaches for detecting adulteration and ensuring quality. The study employs standardized experimental procedures, including solubility testing with distilled water and ethyl alcohol, to determine the presence of alcohol and mineral oils such as vaseline or paraffin. Findings indicate that lemon essential oil contains petroleum jelly or paraffin as impurities but no alcohol, highlighting the necessity for stringent quality control. The results underscore the importance of proper storage and handling to prevent oxidation and degradation. These findings have significant implications for the pharmaceutical and cosmetic industries, ensuring the safe and effective use of essential oils while reinforcing regulatory standards in quality assurance.